Doping evaluation of InP nanowires for tandem junction solar cells. (14th January 2016) - Lindelöw, F; Heurlin, M; Otnes, G; Dagytė, V; Lindgren, D; Hultin, O; Storm, K; Samuelson, L; Borgström, M
Abstract: In order to push the development of nanowire-based solar cells further using optimized nanowire diameter and pitch, a doping evaluation of the nanowire geometry is necessary. We report on a doping evaluation of n-type InP nanowires with diameters optimized for light absorption, grown by the use of metal–organic vapor phase epitaxy in particle-assisted growth mode using tetraethyltin (TESn) as the dopant precursor. The charge carrier concentration was evaluated using four-probe resistivity measurements and spatially resolved Hall measurements. In order to reach the highest possible nanowire doping level, we set the TESn molar fraction at a high constant value throughout growth and varied the trimethylindium (TMIn) molar fraction for different runs. Analysis shows that the charge carrier concentration in nanowires grown with the highest TMIn molar fraction (not leading to kinking nanowires) results in a low carrier concentration of approximately 10 16 cm −3 . By decreasing the molar fraction of TMIn, effectively increasing the IV/III ratio, the carrier concentration increases up to a level of about 10 19 cm −3, where it seems to saturate. Axial carrier concentration gradients along the nanowires are found, which can be correlated to a combination of changes in the nanowire growth rate, measured in situ by optical reflectometry, and polytypism of the nanowires observed in transmission electron microscopy.